Against the tide - Sutherland, Tui, 1978- (Spirit animals, 2014)
Four children have discovered that they have spirit animals, a rare bond between human and animal that has launched them on a quest to save their world, but now they realize that there is a traitor in their midst who has been helping their pursuers and they're heading for a deadly trap.